NURSES’ FATIGUE IN IN VITRO FERTILIZATION (IVF) SERVICE PROVISION: A CASE STUDY AT A FERTILITY CENTRE IN INDONESIA - Hinting, Lia Natalia; Kristianingsih, Rey; Sadewo, Ageng Bagus; Setijowatie, Eva Diah; Dewanto, Aryo; Hariyanti, Tita (Universitas Brawijaya, 2025)
Infertility patients encounter stress stemming from their challenges in conceiving. This makes patients more sensitive when interacting with healthcare providers, especially nurses, during the IVF program. However, professional nursing care puts strain on nurses, leading to fatigue. The causes and coping mechanisms of nurse fatigue are examined in this study. This qualitative exploratory study was conducted at a hospital in Surabaya, Indonesia, known for its excellent IVF treatments. In-depth, semi-structured interviews were conducted with fifteen purposive-sampled nurses. Transcription and theme analysis were performed on the recordings. The findings revealed that all nurses involved in the study experienced burnout with six themes: personal characteristics, adaptability, managing heavy workloads, intention to continue working, and internal and external factors contributing to fatigue. The interconnected themes illustrate the professional nursing culture and offer insights into burnout management. Hospital management must acknowledge and mitigate nurse burnout for their well-being, as this directly influences the quality of care delivered.